Rapid preparation method of customizable hydrogel artificial ligament
By using accelerators to promote polymerization and extrusion printing technology in the field of biomedical engineering technology, the rapid customized preparation of high-toughness hydrogels is achieved, and the problem that artificial ligaments in the prior art cannot meet different needs is solved, which significantly improves the mechanical properties.
Patent Information
- Application Number
- CN202411945144.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing artificial ligaments cannot meet the needs of artificial ligaments from different ages and gender groups and different parts of the human body, and cannot achieve customized preparation.
By using accelerators to promote rapid polymerization of monomers under the action of initiators, combined with extrusion printing technology, the rapid gelation and customized shape and size preparation of high-toughness hydrogels are achieved.
It realizes rapid preparation of high-toughness hydrogels and customization of shape and size, meets the needs of different groups and parts, and shows excellent mechanical properties.
Smart Images

Figure CN119733098A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical engineering, and in particular to a method for rapidly preparing a customizable hydrogel artificial ligament. Background Art
[0002] The anterior cruciate ligament (ACL) is the main dynamic stabilizing structure for knee flexion and rotation, and plays an extremely important role in maintaining knee stability. In recent years, the incidence of sports injuries to the anterior cruciate ligament of the knee has increased year by year, and it can cause serious complications such as meniscus injury and traumatic osteoarthritis. The commonly used treatment method is to reconstruct the ACL through surgery to restore knee function and allow patients to resume normal activities. At present, the most common ACL reconstruction grafts in clinical practice mainly include autologous grafts, allografts and artificial ligaments.
[0003] Autologous grafts are ligaments and tendon tissues extracted from other parts of the patient's body according to the length of the ligament to be reconstructed by the patient during surgery. It has no risk of disease transmission, no immune rejection, and excellent mechanical properties, but it has the disadvantages of limited sources, secondary damage to the sampling site, many complications, and a long recovery period. Allografts are taken from allogeneic tissues, which avoids secondary trauma to the patient, but there are risks such as disease transmission and immune rejection, and the quality is uneven and the cost is expensive. Artificial ligaments have the characteristics of high strength and low rejection, and have gradually become the first choice for ACL reconstruction. They mainly include synthetic polymer fibers, carbon fibers, etc. However, the existing artificial ligaments cannot meet the needs of people of different ages and genders and different parts of the human body for artificial ligaments. Therefore, it is crucial to quickly prepare customized artificial ligaments with adjustable mechanical properties / geometric dimensions. Summary of the invention
[0004] In view of the technical gap that artificial ligaments in the prior art cannot be customized, the present invention provides a method for quickly preparing a customizable hydrogel artificial ligament.
[0005] The method for rapidly preparing a customizable hydrogel artificial ligament provided by the present invention comprises the following steps:
[0006] S1. Add thickener A into solvent A to form a thickener dispersion. The solvent A is one of water, DMF or NMP.
[0007] S2. Add an accelerator to the thickener dispersion, stir and mix evenly to obtain a mixed solution A; the accelerator is selected from one or a combination of ascorbic acid, ferrous sulfate, ferrous chloride, and MXene.
[0008] S3, add polymerizable monomer, crosslinking agent and thickener B to mixed solution A, stir and mix evenly to obtain mixed solution B; the monomer is selected from one or a combination of acrylic acid, acrylamide, sodium p-styrene sulfonate, methyl methacrylate, and the crosslinking agent is selected from N,N'-methylenebisacrylamide or polyethylene glycol acrylate. The thickener A and thickener B are both selected from one of hydroxypropyl methylcellulose, carboxymethyl cellulose, starch ether, polyvinyl alcohol, sodium polyacrylate, and polyacrylamide. The types of thickener A and thickener B can be the same or different.
[0009] S4. Use mixed liquid B as printing ink, and extrude the ink directly into an aqueous solution containing an initiator by extrusion printing to obtain a tough hydrogel. The tough hydrogel is then rinsed with deionized water and then cross-linked to obtain an artificial ligament. The extrusion printing method can control the different geometric dimensions of the tough hydrogel to obtain a customized artificial ligament.
[0010] The extrusion printing method can be one of pneumatic, piston or screw. During printing, the needle moves at a speed of 5-20 mm / s relative to the substrate, the gap between the needle and the substrate is 50 μm-400 μm, and the substrate is made of quartz glass, organic glass or polytetrafluoroethylene. After printing, the reaction temperature is 30°C-90°C, and the reaction time is 30min-120min.
[0011] Preferably, in step S1, the mass percentage concentration of thickener A in the thickener dispersion is 2%-10%.
[0012] Preferably, the total amount of thickener A and thickener B is 4%-7% of the total mass of the ink.
[0013] Preferably, the amount of the accelerator accounts for 1‰-5‰ of the total mass of the ink.
[0014] Preferably, the amount of the monomer accounts for 20%-90% of the total mass of the ink. The mass ratio of the cross-linking agent to the monomer is 1:(350-700).
[0015] Preferably, the initiator is ammonium persulfate, and the mass percentage concentration of the initiator in the aqueous solution is 6%-15%.
[0016] Compared with the prior art, the present invention is beneficial in that:
[0017] The method of the present invention uses an accelerator to promote the rapid polymerization reaction of monomers under the action of an initiator, thereby achieving rapid gelation of high-toughness hydrogels, and combines extrusion printing to achieve the preparation of high-toughness hydrogels customized in shape and size. This customizable high-toughness hydrogel exhibits excellent mechanical properties in the application scenario of artificial ligaments. It successfully solves the problem that existing artificial ligaments cannot meet the ligament needs of people of different genders, ages, and different parts of the human body.
[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a real shot of the artificial ligament prepared in Example 1.
[0020] Figure 2 This is the tensile stress-strain curve of the artificial ligament prepared in Example 1.
[0021] Figure 3 This is a real shot of the artificial ligament prepared in Example 1 being used to repair the anterior fork ligament of a pig.
[0022] Figure 4 This is the stress-strain curve of the joint after anterior cruciate ligament repair. DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0024] Example 1
[0025] Preparation and performance testing of polyacrylic acid high-toughness hydrogel artificial ligament. The preparation steps are as follows:
[0026] S1: dispersing hydroxypropyl methylcellulose powder in water to form an aqueous dispersion having a hydroxypropyl methylcellulose mass concentration of 5%, i.e., a thickener dispersion;
[0027] S2. Take 2 g of the thickener dispersion, add 50 mg of ferrous sulfate (accelerator) thereto, and stir in a rotary mixer at a speed of 2000 rpm for 1 h to obtain a mixed solution A.
[0028] S3. Add 20 g of acrylic acid monomer, 5 mg of N,N'-methylenebisacrylamide and 1 g of hydroxypropyl methylcellulose powder to the mixed solution A, and stir the mixture in a rotary mixer at a speed of 2000 rpm for 2 h to obtain a mixed solution B.
[0029] S4. Use mixed solution B as printing ink, and use pneumatic extrusion printing method to extrude the ink directly into the aqueous solution containing ammonium persulfate to obtain tough hydrogel. The printing pressure is set to 200kPa, the needle moves at a speed of 10mm / s relative to the substrate during printing, the gap between the needle and the substrate is 200μm, the substrate is made of organic glass, and the mass percentage concentration of ammonium persulfate in the aqueous solution is 10%; after printing, rinse with running deionized water for 5 minutes, then use absorbent paper to absorb the surface moisture, and cross-link at 40°C for 60 minutes to obtain Figure 1 The hydrogel artificial ligament shown.
[0030] The artificial ligament was subjected to tensile stress and strain tests using a universal testing machine at a tensile rate of 50 mm / min. The test results are shown in Figure 2 The maximum tensile deformation of the intrinsic hydrogel artificial ligament is 220%, the tensile strength is 1.48MPa, and the modulus is about 0.67MPa.
[0031] The artificial ligament prepared in Example 1 was used to reconstruct the anterior fork ligament of the pig leg: Figure 3 As shown in the figure, fresh pig legs were purchased from the market. First, the muscles, patella, infrapatellar fat and joint capsule at the knee were removed, and the collateral ligament, medial meniscus, lateral meniscus and two cruciate ligaments were retained. The anterior cruciate ligament was cut short, and then a twist drill with a diameter of 5.0 mm was used to create two bone tunnels in the tibial and femoral footprints. Two artificial ligaments (20 cm long, 6 mm wide, and 0.5 mm thick) were passed through the bone tunnels to replace the anterior cruciate ligament and fixed with two polyetherketone interface screws. The stress-strain curve of the joint after anterior cruciate ligament repair is shown in Figure 2. Figure 4 The repaired joint ligaments include the lateral collateral ligament and the anterior cruciate ligament replaced by hydrogel. With the assistance of these two ligaments, the repaired knee joint can withstand a force of 60kg without being damaged.
[0032] Example 2
[0033] Preparation of polyacrylamide high-toughness hydrogel artificial ligament:
[0034] S1: dispersing hydroxypropyl methylcellulose powder in water to form an aqueous dispersion having a hydroxypropyl methylcellulose mass concentration of 5%, i.e., a thickener dispersion;
[0035] S2. Take 2 g of the thickener dispersion, add 30 mg of MXene (accelerator) thereto, and stir in a rotary mixer at a speed of 2000 rpm for 1 h to obtain a mixed solution A.
[0036] S3. Add 5 g of acrylamide monomer, 10 g of water, 5 mg of N,N'-methylenebisacrylamide and 1 g of hydroxypropyl methylcellulose powder to the mixed solution A, and stir the mixture in a rotary mixer at a speed of 2000 rpm for 2 h to obtain a mixed solution B.
[0037] S4. Use mixed liquid B as printing ink, and use pneumatic extrusion printing method to extrude the ink directly into an aqueous solution containing ammonium persulfate to obtain a tough hydrogel; the printing air pressure is set to 300 kPa, the needle moves at a speed of 5 mm / s relative to the substrate during printing, the gap between the needle and the substrate is 300 μm, and the substrate is made of plexiglass; the mass percentage concentration of ammonium persulfate in the aqueous solution is 6%; after printing, rinse with running deionized water for 5 minutes, then use absorbent paper to absorb the surface moisture, and cross-link at 50°C for 30 minutes to obtain a hydrogel artificial ligament.
[0038] Example 3
[0039] Preparation of polyacrylic acid high-toughness hydrogel artificial ligament:
[0040] S1: dispersing polyvinyl alcohol in water to form an aqueous dispersion having a mass percent concentration of 5%, i.e., a thickener dispersion;
[0041] S2. Take 2 g of the thickener dispersion, add 30 mg of MXene (accelerator) thereto, and stir in a rotary mixer at a speed of 2000 rpm for 1 h to obtain a mixed solution A.
[0042] S3. Add 20 g of acrylic acid monomer, 5 mg of N,N'-methylenebisacrylamide and 1 g of hydroxypropyl methylcellulose powder to the mixed solution A, and stir the mixture in a rotary mixer at a speed of 2000 rpm for 2 h to obtain a mixed solution B.
[0043] S4. Use mixed liquid B as printing ink, and use pneumatic extrusion printing method to extrude the ink directly into an aqueous solution containing ammonium persulfate to obtain a tough hydrogel; the printing air pressure is set to 100 kPa, the needle moves at a speed of 8 mm / s relative to the substrate during printing, the gap between the needle and the substrate is 300 μm, the substrate is made of plexiglass, and the mass percentage concentration of ammonium persulfate in the aqueous solution is 15%; after printing, rinse with running deionized water for 5 minutes, then use absorbent paper to absorb the surface moisture, and cross-link at 50°C for 40 minutes to obtain a hydrogel artificial ligament.
[0044] Comparative Example 1
[0045] On the basis of Example 1, the addition of ferrous sulfate (accelerator) was omitted, and other steps remained unchanged to obtain an artificial ligament.
[0046] Comparative Example 2
[0047] The dosage of each raw material and reagent is exactly the same as that in Example 1, and the preparation method is as follows:
[0048] Step S1: 50 mg of ferrous sulfate (accelerator), 20 g of acrylic acid monomer, 5 mg of N,N'-methylenebisacrylamide, and 1.1 g of hydroxypropyl methylcellulose powder were added to 1.9 g of water, and stirred at 2000 rpm in a rotary mixer for 2 h to obtain a mixed solution.
[0049] Step S2, using the mixed liquid as printing ink, and using a pneumatic extrusion printing method to extrude the ink directly into an aqueous solution containing ammonium persulfate to obtain a tough hydrogel; the printing air pressure is set to 200 kPa, the needle moves at a speed of 10 mm / s relative to the substrate during printing, the gap between the needle and the substrate is 200 μm, the substrate is made of organic glass, and the mass percentage concentration of ammonium persulfate in the aqueous solution is 10%; after printing is completed, rinse with running deionized water for 5 minutes, then use absorbent paper to absorb surface moisture, and cross-link at 40° C. for 60 minutes to obtain an artificial ligament.
[0050] Comparative Example 3
[0051] On the basis of Example 1, in step S4, a pneumatic extrusion printing method is used to extrude the ink directly into pure water without an initiator. The results show that due to the lack of an initiator, the monomer cannot undergo a polymerization reaction and an artificial ligament cannot be formed.
[0052] The artificial ligaments prepared in Examples 1-3 and Comparative Examples 1 and 2 were tested for properties such as toughness, strength and elongation. The results are shown in Table 1.
[0053] Table 1. Comparison of the performance of artificial ligaments prepared in Examples 1-3 and Comparative Examples 1 and 2
[0054] <![CDATA[Toughness (kJ / m 2 )]]> Strength (MPa) Elongation (%) Example 1 12.5 1.48 220 Example 2 75.2 2.35 2300 Example 3 6.72 0.53 725 Comparative Example 1 0.12 0.08 135 Comparative Example 2 0.04 0.03 526
[0055] The data in the table show that the artificial ligament preparation method of the present invention is universal and can be applied to the customized rapid preparation of artificial ligaments of different geometric sizes and chemical components; and the toughness of the artificial ligament prepared by the present invention is relatively high and adjustable. It can be seen from Comparative Example 1 that if no accelerator is added to the preparation method, the toughness, strength, elongation and other properties of the prepared artificial ligament will be greatly reduced. This is because the accelerator in the preparation method of the present invention can promote the acceleration of the polymerization reaction of the monomer, and then quickly polymerize to prepare a high-toughness hydrogel artificial ligament. It can be seen from Comparative Example 2 that if the thickener is added at one time in the preparation method, the toughness, strength and elongation and other properties of the prepared artificial ligament will also be greatly reduced. This shows that the preparation method of the present invention, adding the thickener in batches at different times will be beneficial to improving the comprehensive performance of the artificial ligament.
[0056] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for rapidly preparing a customizable hydrogel artificial ligament, characterized in that: The following steps are involved: S1, adding thickener A to solvent A to form a thickener dispersion; S2. Add an accelerator to the thickener dispersion, stir and mix evenly to obtain a mixed solution A; the accelerator is selected from one or a combination of ascorbic acid, ferrous sulfate, ferrous chloride, and MXene; S3, adding a polymerizable monomer, a crosslinking agent and a thickener B to the mixed solution A, stirring and mixing to obtain a mixed solution B; the monomer is selected from one or a combination of acrylic acid, acrylamide, sodium p-styrene sulfonate, and methyl methacrylate, and the crosslinking agent is selected from N,N'-methylenebisacrylamide or polyethylene glycol acrylate; S4. Use mixed liquid B as printing ink, and extrude the ink directly into an aqueous solution containing an initiator by extrusion printing to obtain a tough hydrogel. The tough hydrogel is then rinsed with deionized water and then cross-linked to obtain an artificial ligament. The extrusion printing method can control the different geometric dimensions of the tough hydrogel to obtain a customized artificial ligament.
2. The method for rapidly preparing a customizable hydrogel artificial ligament according to claim 1, characterized in that: The thickener A and the thickener B are both selected from one of hydroxypropyl methylcellulose, carboxymethyl cellulose, starch ether, polyvinyl alcohol, sodium polyacrylate and polyacrylamide.
3. The rapid preparation method of a customizable hydrogel artificial ligament according to claim 2, characterized in that: The solvent A is one of water, DMF or NMP.
4. The rapid preparation method of a customizable hydrogel artificial ligament according to claim 3, characterized in that: In step S1, the mass percentage concentration of thickener A in the thickener dispersion is 2%-10%.
5. The rapid preparation method of a customizable hydrogel artificial ligament according to claim 1, characterized in that: The total amount of thickener A and thickener B is 4%-7% of the total mass of the ink.
6. The method for rapidly preparing a customizable hydrogel artificial ligament according to claim 1, characterized in that: The amount of the accelerator is 1‰-5‰ of the total mass of the ink.
7. The rapid preparation method of a customizable hydrogel artificial ligament according to claim 1, characterized in that: The amount of the monomer accounts for 20%-90% of the total mass of the ink.
8. The method for rapidly preparing a customizable hydrogel artificial ligament according to claim 7, characterized in that: The mass ratio of the cross-linking agent to the monomer is 1:(350-700).
9. The method for rapidly preparing a customizable hydrogel artificial ligament according to claim 1, characterized in that: The extrusion printing method is one of pneumatic, piston or screw.
10. The rapid preparation method of a customizable hydrogel artificial ligament according to claim 1, characterized in that: The initiator is ammonium persulfate, and the mass percentage concentration of the initiator in the aqueous solution is 6%-15%.
Citation Information
Patent Citations
Preparation method of agar / polyacrylamide dihydrogen bond cooperative crosslinking high-tenacity hydrogel capable of 3D printing
CN108276590A
Mechanical toughening method based on polyvinyl alcohol double-network material, toughening material and application of toughening material
CN118791756A
Method for preparing hydrogel by rapidly initiating free radical polymerization of hydrophilic monomer
CN118930699A
Dynamic hydrogel compositions
WO2024102853A1
Cited By
Preparation method of hydrogel strain sensor capable of being subjected to 4D printing
CN121018931A